Underwater Endoscopic Mucosal Resection of Small Rectal Neuroendocrine Tumors - Masahiro Okada; Satoshi Shinozaki; Satoshi Shinozaki; Eriko Ikeda; Eriko Ikeda; Yoshikazu Hayashi; Takahito Takezawa; Hisashi Fukuda; Takaaki Morikawa; Masafumi Kitamura; Munefumi Arita; Tatsuma Nomura; et al. (Frontiers in Medicine, 2022)
Background and Study AimsThe resection strategy for rectal neuroendocrine tumors (NET) < 10 mm is not uniform. We compared the utility of underwater endoscopic mucosal resection (UEMR) to endoscopic submucosal resection with a ligation device (ESMR-L) to resect rectal NETs.Patients and MethodsPatients with rectal NET < 10 mm treated with UEMR or ESMR-L were included. Their medical records were retrospectively reviewed.ResultsThirty-two patients were divided into a UEMR group (n = 7) and an ESMR-L group (n = 25). Histopathological diagnosis of NET by biopsy was known before resection in 43% (3/7) in the UEMR group and 68% (17/25) in the ESMR-L group, (p = 0.379). UEMR was performed on an outpatient basis for all patients, and 92% of ESMR-L (23/25) were performed as inpatient procedures (p < 0.001). The procedure time was significantly shorter in the UEMR group than in the ESMR-L group [median (IQR), min, 6 (5–8) vs. 12 (9–14), p = 0.002]. En bloc resection and R0 resection rates were 100% in both groups. Pathological evaluations were predominantly NET G1 in both groups (UEMR: 7/7, 100% and ESMR-L: 23/25, 92%). Two patients in the ESMR-L group developed delayed bleeding, controlled by endoscopic hemostasis. Device costs were significantly higher in the ESMR-L group than the UEMR group by approximately US$180 [median (IQR), $90.45 (83.64–108.41) vs. $274.73 (265.86–292.45), P < 0.001].ConclusionUEMR results in similar resection quality with shorter procedure time and lower costs compared to ESMR-L. We recommend UEMR for the resection of rectal NET < 10 mm.